2022
DOI: 10.1002/ar.25047
|View full text |Cite
|
Sign up to set email alerts
|

Osteohistology of Dromornis stirtoni (Aves: Dromornithidae) and the biological implications of the bone histology of the Australian mihirung birds

Abstract: The late Miocene Dromornis stirtoni is the largest of the giant flightless dromornithid birds. Here, we studied 22 long bones (femora, tibiotarsi, tarsometatarsi) of D. stirtoni to assess its osteohistology to deduce various aspects of its life history. Our results show that D. stirtoni took several years (likely, more than a decade), to reach adult body size, after which its growth rate slowed down, and skeletal maturity occurred. This growth strategy differs from that of its Pleistocene relative, Genyornis n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…Rather, to name just some, they span a glorious gamut: from detailed descriptions of unusual Therapods from New Jersey (really? hadrosaurs, Jimmy Hoffa…who knew Jersey was actually interesting; sorry, JL is a native New Yorker and has little control when commenting on New Jersey; Gallagher, 2023); reports on a new iguanodontian dinosaur from South Africa (Forster et al, 2023); new insights on evolutionary relationships from analyses of the hyolaryngeal apparatus in extant archosaurs (i.e., birds and crocodilians; Yoshida et al, 2023); new reconstructions of the pectoral girdle and forelimb musculature of Megaraptora (Rolando et al, 2023); insights from osteohistology of Dromornis stironi with implications for understanding the histology of Australian mihirung birds (Chinsamy et al, 2023); insightful observations on fracture and disease in a large‐bodied ornithomimosaur with insights into identifying unusual endosteal bone in the fossil record (Chinzorig et al, 2023); a comprehensive assessment of the history and future of the study of morphometrics in the study on non‐avian dinosaurs (Hedrick, 2023); detailed modeling to assess and predict the abundance of large carnivorous dinosaurs of the Upper Jurassic Morrison Formation and the Upper Cretaceous Dinosaur Park formation (by Peter and JL's Yale classmate, the ever‐creative James Farlow; JL is still in awe at all the super‐bright dino dudes that surrounded him at Yale “back in the day”; Farlow et al, 2023); to a number of papers—naturally—on Peter's great love, the ceratopsians, including those by lead Guest Editor Fiorillo (Fiorillo & Tykoski, 2023) and Peter's successor teaching anatomy at Penn, Ali Nabavizadeh (Nabavizadeh, 2023). Even the cover of this Special Issue has been a creative homage to Peter, lovingly created by Anatomical Record Associate Editor (and artist extraordinaire) Adam Hartstone‐Rose (Hartstone‐Rose et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…Rather, to name just some, they span a glorious gamut: from detailed descriptions of unusual Therapods from New Jersey (really? hadrosaurs, Jimmy Hoffa…who knew Jersey was actually interesting; sorry, JL is a native New Yorker and has little control when commenting on New Jersey; Gallagher, 2023); reports on a new iguanodontian dinosaur from South Africa (Forster et al, 2023); new insights on evolutionary relationships from analyses of the hyolaryngeal apparatus in extant archosaurs (i.e., birds and crocodilians; Yoshida et al, 2023); new reconstructions of the pectoral girdle and forelimb musculature of Megaraptora (Rolando et al, 2023); insights from osteohistology of Dromornis stironi with implications for understanding the histology of Australian mihirung birds (Chinsamy et al, 2023); insightful observations on fracture and disease in a large‐bodied ornithomimosaur with insights into identifying unusual endosteal bone in the fossil record (Chinzorig et al, 2023); a comprehensive assessment of the history and future of the study of morphometrics in the study on non‐avian dinosaurs (Hedrick, 2023); detailed modeling to assess and predict the abundance of large carnivorous dinosaurs of the Upper Jurassic Morrison Formation and the Upper Cretaceous Dinosaur Park formation (by Peter and JL's Yale classmate, the ever‐creative James Farlow; JL is still in awe at all the super‐bright dino dudes that surrounded him at Yale “back in the day”; Farlow et al, 2023); to a number of papers—naturally—on Peter's great love, the ceratopsians, including those by lead Guest Editor Fiorillo (Fiorillo & Tykoski, 2023) and Peter's successor teaching anatomy at Penn, Ali Nabavizadeh (Nabavizadeh, 2023). Even the cover of this Special Issue has been a creative homage to Peter, lovingly created by Anatomical Record Associate Editor (and artist extraordinaire) Adam Hartstone‐Rose (Hartstone‐Rose et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…Although several histological studies have focused on growth dynamics of either extant or extinct taxa, few studies have investigated a single species over a long period of its evolutionary history (e.g. [52]). Moreover, although histological studies on chelonian limb bones and/or shell bones have been used to determine skeletochronology and reconstruct growth rates of the testudines [48,49,[53][54][55][56][57][58][59][60][61][62], histological data from a single species, involving both modern and fossilized individuals is non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…But at approximately 79 million years old, the Wendiceratops bonebed is close to 2 million years older than other ceratopsid bonebeds making this occurrence the oldest documented evidence of herding behavior in any ceratopsid (Scott et al, 2023). Chinsamy et al (2023) studied the late Miocene Dromornis stirtoni, the largest of the giant flightless dromornithid birds. They showed that this taxon took several years, perhaps, more than a decade, to reach adult body size, a strategy that differed from Genyornis newtoni, a Pleistocene relative that had faster rates of growth in achieving adult body size (Chinsamy et al, 2023).…”
mentioning
confidence: 99%
“…They showed that this taxon took several years, perhaps, more than a decade, to reach adult body size, a strategy that differed from Genyornis newtoni, a Pleistocene relative that had faster rates of growth in achieving adult body size (Chinsamy et al, 2023). The authors suggest that these mihirung birds, separated by millions of years, each responded to the prevailing environmental conditions of their respective time (Chinsamy et al, 2023). Tsogtbaatar et al (2023) describe the external gross morphology and internal architecture of a pathologic right second metatarsal of a Cretaceous large-bodied ornithomimid from Mississippi.…”
mentioning
confidence: 99%
See 1 more Smart Citation